Schools of sympathy : gender and identification through the novel - Roberts, Nancy, 1948- (McGill-Queen's University Press, 1997)
"Schools of Sympathy is a feminist exploration of gender and identification in Samuel Richardson's Clarissa, Nathaniel Hawthorne's The Scarlet Letter, Henry James's Portrait of a Lady, and Thomas Hardy's Tess of the d'Urbervilles. In each of these novels the heroine is portrayed as a victim. Nancy Roberts examines how the reader's sympathy for the heroines is constructed, the motivations and desires involved in an identification with victimization, and the gender and power roles that such an identification calls into play."--Jacket